Experiential Learning to Promote Student Autonomy at Elementary Level - Hossain, Shaukat Ali; Manzoor, Mehmood Ahmed; Hashmi, Rozina (Papanda Publisher, 2023)
The primary objective of this research is to assess Learners' Autonomy by implementing Experiential Learning in a role-play activity among class 8 elementary students at a private-sector English Medium School. Experiential Learning, which is a learner-friendly approach, has not been extensively explored at the fundamental level. However, its importance, often referred to as